MINAT PETANI TERHADAP PENGGUNAAN BIOURINE SEBAGAI PUPUK ORGANIK CAIR PADA TANAMAN BAWANG MERAH (Allium ascalonicum. L) DI KECAMATAN TARUMAJAYA KABUPATEN BEKASI - Andi Marsela Khoir; Endang Krisnawati; Nawangwulan Widyastuti (Jurnal Inovasi Penelitian, 2020)
Tarumajaya District is a center of food crops and horticulture plants where one of the leading commodities of horticultural plants is onion. According to data from the Bekasi Regency Agriculture Office in 2019, the harvest area of shallots in Tarumajaya District is 2,539 Ha, with a production of 15,030.88 tons / ha and productivity of 5.92 tons / ha. The purpose of conducting this study is to describe the interests of farmers, analyze the factors that influence the interests of farmers, and strategies to increase farmers' interest in the use of biourine in shallots. The analysis used is descriptive analysis, simple linear regression analysis and Kendall's W analysis. The results of the analysis show that farmers 'interest in using biourine as liquid organic fertilizer is included in the medium category, factors affecting farmers' interests are farming experience and facilities and infrastructure. The strategy taken to increase the interest of farmers is through extension activities and demonstration plots.